Properties of Generalized $δ p(Λ,s)$-closed Sets (European Journal of Pure and Applied Mathematics, 2023)
This paper deals with the concept of generalized $δ p(Λ,s)$-closed sets. Especially, some properties of generalized $δ p(Λ,s)$-closed sets are discussed. Moreover, we apply the notion of generalized $δ p(Λ,s)$-closed sets to present and study new classes of spaces called $δ p(Λ,s)$-$T_\frac{1}{2}$-spaces and $δ p(Λ,s)$-normal spaces. Several properties and characterizations concerning $δ p(Λ,s)$-$T_\frac{1}{2}$-spaces and $δ p(Λ,s)$-normal spaces are established.
Keywords: $δ p(Λ,s)$-open set; generalized $δ p(Λ,s)$-closed set